2019
DOI: 10.1021/acsnano.9b02917
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Integrated Tubular Microsupercapacitors with Improved Electrochemical Performance and Self-Protective Function

Abstract: Inspired by origami art, we demonstrate a tubular microsupercapacitor (TMSC) by self-assembling two-dimensional (2D) films into a "swiss roll" structure with greatly reduced footprint area. A polymeric framework consisting of swelling hydrogel and polyimide layers ensures excellent ion transport between poly(3,4-ethylenedioxythiophene) (PEDOT)-based electrodes and provides efficient self-protection of the TMSC against external compression up to about 30 MPa. Such TMSCs exhibit an areal capacitance of 82.5 mF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 56 publications
(68 reference statements)
0
71
0
Order By: Relevance
“…Micro‐supercapacitor (MSC) has gained great attention as an advanced on‐board energy storage system due in part to 1) its in‐plane interdigital configuration that is facilely integrated into wearable on‐chip electronics and integrated circuits, and 2) its outstanding electrochemical performance, such as short response time, long cycling life, fast rate capability, and high power delivery . Moreover, along with the growing demand for miniaturized wearable electronics, a great deal of effort had been devoted to introduce smart functions, such as self‐healing, electrochromism, shape memory, photodetection, thermal responsibility, and stretchability, into the intelligent miniaturized electronics, which exhibited great promise in the future applications of personal healthcare, modern optoelectronics, artificial intelligence, and so on . In order to be utilized in real wearable and intelligent miniaturized electronic applications, the areal electrochemical properties (performance normalized by surface area) for MSCs are more important than the volumetric characteristics due to the limited footprint area available on chips .…”
Section: Introductionmentioning
confidence: 99%
“…Micro‐supercapacitor (MSC) has gained great attention as an advanced on‐board energy storage system due in part to 1) its in‐plane interdigital configuration that is facilely integrated into wearable on‐chip electronics and integrated circuits, and 2) its outstanding electrochemical performance, such as short response time, long cycling life, fast rate capability, and high power delivery . Moreover, along with the growing demand for miniaturized wearable electronics, a great deal of effort had been devoted to introduce smart functions, such as self‐healing, electrochromism, shape memory, photodetection, thermal responsibility, and stretchability, into the intelligent miniaturized electronics, which exhibited great promise in the future applications of personal healthcare, modern optoelectronics, artificial intelligence, and so on . In order to be utilized in real wearable and intelligent miniaturized electronic applications, the areal electrochemical properties (performance normalized by surface area) for MSCs are more important than the volumetric characteristics due to the limited footprint area available on chips .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the self‐protective MSC with a polymeric framework consisting of swelling hydrogel and polyimide layers have been designed. [ 168 ] A self‐healable MSC was prepared by assembling the ice‐templated 3D MXene‐rGO composite aerogels with the PVA/H 2 SO 4 gel electrolyte and the self‐healing CPU shell (Figure 13c). The MSC exhibited a capacity retention of 81.7% after five cutting–healing cycles.…”
Section: Hydrogen Bond Based Self‐healing Materials For Esdsmentioning
confidence: 99%
“… By varying the 2D pattern and origami design, they successfully realized the integration of a foldable system that can be applied in multifunctional electronics such as energy harvesting, gas sensing, and energy storage. Also inspired by origami, Want et al demonstrated tubular MSCs based on rolled‐up technology . The PEDOT electrodes were self‐assembled into a “swiss roll” structure, and hydrogel frameworks were wrapped around the electrodes ensuring excellent ion transport.…”
Section: D Stereo Mscsmentioning
confidence: 99%